Astragalus Polysaccharides Enhance the Immune Response to OVA Antigen in BALB/c Mice. (29th June 2021) - Zhou, Yumei; Zong, Yuhan; Liu, Zihao; Zhao, Haihong; Zhao, Xiaoshan; Wang, Ji
Abstract : Vaccination has been identified as one of the most effective ways to prevent the transmission of infectious diseases in humans and animals. One of the most critical steps in vaccine development is the selection of a suitable adjuvant. Although various adjuvant candidates have been evaluated in the past few decades, only a limited amount of them are nontoxic and safe for human use. Astragalus polysaccharide (APS), due to its lack of toxicity, has been used as an immunomodulator to enhance immune responses. On the other hand, the immune effects of APS on ovalbumin are yet to be examined. Thus, in this study, we analyzed APS's effects on the immune response to ovalbumin in BALB/c mice. We have also used the classic adjuvant CpG oligodeoxynucleotide as the positive control.